Detection of perilymphatic fistula in labyrinthine windows by virtual endoscopy and variation of reconstruction thresholds on CT scan. (2nd April 2020) - Bozorg Grayeli, Alexis; Bensimon, Jean-Loup; Guyon, Maxime; Aho-Glele, Serge; Toupet, Michel
Abstract: Background: Perilymphatic fistula (PLF) is a breach in a labyrinthine window. The opening might decrease the radiological density of the window. Aims/objectives: To evaluate the radiological density of the labyrinthine windows by virtual endoscopy on CT scan. Materials and methods: This prospective study included 47 adult patients with PLF and 98 control patients. Diagnosis of PLF was based on a composite radio clinical score and/or intra operative visualization of the fistula and/or resolution of the symptoms after surgery. On routine CT-scan, labyrinthine windows were examined by virtual endoscopy. The reconstruction threshold was gradually increased until a virtual opening appeared (opening threshold [OT]) and compared to the contralateral window (OT difference). Results: The OT difference was higher in patients than in controls (60.2 ± 10.36 (SEM), n = 47 versus 28.0 ± 2.29 Hounsfield units (HUs), n = 98, p < .01 unpaired t -test). A ROC analysis showed that at an OT difference of 31.5 UH had a sensitivity of 75% and a specificity of 75% for the PLF diagnosis. Conclusions: CT-scan virtual endoscopy and threshold variation provided high specificity and sensitivity in the PLF diagnosis. Significance: This post processing of radiological data appears to enhance the diagnostic value of CT scan.